Staff Burnout and Leadership Styles towards Job Performance during Critical Period - Aflinda Mokhtar; Noor’ain Mohamad Yunus (Information Management and Business Review, 2023)
Recent pandemic of COVID-19 has heightened the need for mental and emotional health and the demands for specific types of leadership styles toward performance. The researcher believes that burnout and leadership styles are interrelated towards the job and the organization’s performance during the critical period. Hence, this study aims to investigate the relationship between staff burnout and leadership styles toward job performance during the critical Movement Control Order (MCO) period due to COVID-19 in Malaysia. A questionnaire was used as the main instrument in the data collection process. A total of 180 online surveys in the form of Google Form format were distributed among Credit Guarantee Corporation Malaysia Berhad (CGC) employees through a convenience sampling technique. Multiple regression analysis was used to investigate the relationship between determinants of staff burnout and leadership styles toward job performance. The data collected was analyzed using SmartPLS, one of the most popular software applications for Partial Least Squares Structural Equation Modelling (PLS-SEM). The result indicated a significant relationship between burnout (personal accomplishment) and leadership styles (autocratic, democratic, and laissez-faire) toward job performance. In comparison, burnout (emotional exhaustion and depersonalization) has no significant relationship with job performance. The researcher suggested that future research conduct another study with different populations of respondents by considering the larger sample size, including all levels of employees in an organization from all the companies in the same industries.